2023
DOI: 10.1038/s41598-023-38826-y
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth characterisation of European seabass intestinal segments for assessing the impact of an algae-based functional diet on intestinal health

Abstract: Sustainable farming of fish species depends on emerging new feed ingredients, which can alter the features of the digestive tract and influence animals’ overall health. Recent research has shown that functional feeds hold great potential for enhancing fish robustness by evoking appropriate responses at the intestine level. However, there is a lack of extensive and accurate descriptions of the morphology of the gastrointestinal tract of most farmed fish. We have characterised the intestine of European seabass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Medicinal plants such as Yucca schidigera improved hematological parameters and immunological responses [ 33 ], while the introduction of prebiotics acted as immunostimulants through the increase of phagocytic activity [ 34 ]. It was also suggested that dietary supplementation with a macro- and microalgae blend may improve the intestinal health of D. labrax [ 35 ]. Recently, a study investigated the use of alternative feed resources from insects, crustacea, or microalgae biomass as functional supplements in a diet for juvenile D. labrax totally deprived of fish meal [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants such as Yucca schidigera improved hematological parameters and immunological responses [ 33 ], while the introduction of prebiotics acted as immunostimulants through the increase of phagocytic activity [ 34 ]. It was also suggested that dietary supplementation with a macro- and microalgae blend may improve the intestinal health of D. labrax [ 35 ]. Recently, a study investigated the use of alternative feed resources from insects, crustacea, or microalgae biomass as functional supplements in a diet for juvenile D. labrax totally deprived of fish meal [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Gilbert [153], rotifers are subdivided into four categories as defined by types of food ingested: (1) nanoplankton, (2) microplankton, (3) 5-50 µm algae, and (4) 5-Fishes 2024, 9, 63 13 of 21 250 µm algae. Larval rearing of marine fish, for example, turbot (Scophthalmus maximus) and Atlantic halibut (Hippoglossus hippoglossus), can result in a bottleneck, and at this early life stage, it is important to transfer essential nutrients from algae to live food [154]. The reference to Yan et al [155] likely provides valuable insights into the specific methodologies, experimental setups, and findings related to using rotifers for toxicity testing of harmful algae.…”
Section: Rotifers and Algaementioning
confidence: 99%